2017
DOI: 10.24912/jm.v21i1.148
|View full text |Cite
|
Sign up to set email alerts
|

Bauran Pemasaran Kepuasan Dan Loyalitas Pelanggan Benih Kelapa Sawit Pt Socfin Indonesia

Abstract: Along with the increasing demand of palm oil seed trigger an increased number of seed producers of palm oil in Indonesia. Under conditions of tight competition, PT Socfin Indonesia (Socfindo) as one of the producers of palm oil seed needs to evaluate the performance of the marketing mix (product, price, place and promotion) through customer satisfaction and loyalty. This study aimed to analyze the influence of marketing mix towards customer satisfaction and loyalty as well as to analyze the level of satisfacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
1
Order By: Relevance
“…The research by (Pupuani and Sulistyawati, 2013) with toothpaste products in Denpasar as the object of research revealed that the marketing mix with 4P elements had a positive and significant effect on consumers' satisfaction. This is in contrast to the research by (Safitri et al, 2017) which showed that only products in the marketing mix element had a positive and significant effect.…”
Section: Research Hypothesis H1contrasting
confidence: 99%
“…The research by (Pupuani and Sulistyawati, 2013) with toothpaste products in Denpasar as the object of research revealed that the marketing mix with 4P elements had a positive and significant effect on consumers' satisfaction. This is in contrast to the research by (Safitri et al, 2017) which showed that only products in the marketing mix element had a positive and significant effect.…”
Section: Research Hypothesis H1contrasting
confidence: 99%
“…Hermawan (2015) stated that consumer satisfaction is influenced by prices and products, which affects loyalty. Safitri, Suharno, Fariyanti (2017) said that the mixed marketing variable significantly affects customer satisfaction and loyalty of oil palm seeds. Wahab, Abu Hassab, Shahid, Maon (2015) argued that the 4P mix marketing (product, price, place, promotion) has a close relationship.…”
Section: Agricultural Sciencementioning
confidence: 99%